2015
DOI: 10.14700/kitla.2015.33.4.087
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Synecological Values of the Torreya nucifera Forest (Natural Monument No. 374) at Pyeongdae-ri in Jeju Island

Abstract: The natural monument forests (no.374) located at Pyeongdae-ri in Jeju island are described and classified by using phytosociological methods and numerical analysis. The purpose of this paper is to identify the ecological character of Torreya nucifera forests between natural habitat and artificial habitat, as well as their spatial and phytogeographical distribution in the Korea. The comparison of forests between Pyeongdae-ri and other regions was analyzed by using a non-metric multidimensional scaling analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Torreya Forest terrain is defined as GujwaSeongsan Gotjawal, a transition lava zone distributing both pahoehoe and aa lava flows (Jeon et al 2012). Although T. nucifera is a domonant species in this forest, the Forest consists of diverse evergreen trees with a total of 276 plant taxa, including Mallotus japonicus, Machilus thunbergii, Orixa japonica, and Polystichum tripteron [Korea Tree Health Association (KTHA) 1999; Lee 2009;Shin et al 2010;Choi and Lee 2015]. Figure 2 demonstrates characteristic features of wild Torreya Forest.…”
Section: Study Species and Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Torreya Forest terrain is defined as GujwaSeongsan Gotjawal, a transition lava zone distributing both pahoehoe and aa lava flows (Jeon et al 2012). Although T. nucifera is a domonant species in this forest, the Forest consists of diverse evergreen trees with a total of 276 plant taxa, including Mallotus japonicus, Machilus thunbergii, Orixa japonica, and Polystichum tripteron [Korea Tree Health Association (KTHA) 1999; Lee 2009;Shin et al 2010;Choi and Lee 2015]. Figure 2 demonstrates characteristic features of wild Torreya Forest.…”
Section: Study Species and Sitementioning
confidence: 99%
“…Gotjawal terrain where Torreya Forest exists is a unique volcanic area with lava blocks scattered extremely disorderly (Jeon et al 2012). Thus, Gotjawal terrain with severe topographic heterogeneity generates highly diverse microclimate (Choi and Lee 2015). Furthermore, Gotjawal terrain represents poor soil development and oligotrophic and stressful environment to plants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of S. prunifolia were undertaken on several occasions during field surveys on Jeju Island and were conducted by universities and arboretums (KBIS 2020; NIBR 2020). In addition, comparative studies of warm temperate zones in Korea and the western regions of Japan found that this species is distributed in two regions that have a high plant geography connection Itow 1996, Choi andLee 2015). Kim and Itow (1996) defined S. prunifolia trees as well as Michelia compressa, Myrica rubra, and Marsdenia tomentosa as the phytogeographic link between the two regions.…”
Section: Introductionmentioning
confidence: 99%